2017
DOI: 10.1097/aog.0000000000001977
|View full text |Cite
|
Sign up to set email alerts
|

Using a Patient Navigator to Improve Postpartum Care in an Urban Women's Health Clinic

Abstract: Objective To estimate whether postpartum visit attendance was improved in women exposed to a postpartum patient navigation program compared with those who received care immediately prior to the program's initiation, and to assess whether other postpartum health behaviors improved during the intervention period. Methods This is a prospective observational study of women enrolled in a patient navigation program compared to women receiving care prior to the program. Navigating New Motherhood was a postpartum pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 21 publications
4
114
0
2
Order By: Relevance
“…27,28 Patient navigation has improved attendance at postpartum visits compared with a historical cohort who did not receive navigation, suggesting applicability to obstetrics, such as for pregnant women who are recommended 17P. 20,29 Additionally, as comprehensive postpartum care represents an ideal opportunity to optimize postpartum health and educate patients about subsequent risks and preventive care, patient navigation for postpartum women with a PTB may be an opportunity to leverage identified facilitators and address barriers to future PTB prevention. 18 Beyond patient navigation, clinicians may use the findings herein to implement several other strategies to improve uptake of and adherence to PTB prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Patient navigation has improved attendance at postpartum visits compared with a historical cohort who did not receive navigation, suggesting applicability to obstetrics, such as for pregnant women who are recommended 17P. 20,29 Additionally, as comprehensive postpartum care represents an ideal opportunity to optimize postpartum health and educate patients about subsequent risks and preventive care, patient navigation for postpartum women with a PTB may be an opportunity to leverage identified facilitators and address barriers to future PTB prevention. 18 Beyond patient navigation, clinicians may use the findings herein to implement several other strategies to improve uptake of and adherence to PTB prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Enrollment in the postpartum navigation program was associated with enhanced postpartum care uptake and frequency of contraception use, vaccination, and depression screening. 36 Whether these interventions are particularly beneficial to women with antenatal depressive symptomatology should be actively explored.…”
Section: Discussionmentioning
confidence: 99%
“…Work by our group on patient navigation suggested that concerted efforts to decrease patient logistical barriers to making and attending postpartum appointments is associated with improved postpartum attendance. 32 However, common patient feedback in this program included the desire for coordinated maternal-newborn care. To address these needs, one strategy is the patient-centered medical home (PCMH), a model which revolves around preventive care and coordination of care.…”
Section: ) Reducing Barriers Via Patient-centered Medical Homementioning
confidence: 99%
“…52 Similarly, our patient navigation program increased postpartum follow-up rates from 70.3% to 88.1% (p<0.001), but there was no statistically significant increase in OGTT completion. 32 A 2012 Kaiser Permanente study, however, sought to combine appointment reminders with other systems processes. 53 The nursing protocol was revised to allow nursing staff to order the tests, and nurse care managers were encouraged to make at least one postpartum reminder call.…”
Section: Developing An Evidence Base For Multilevel Carementioning
confidence: 99%